Higher Tobacco Prices and Taxes in Southeast Asia : An Effective Tool to Reduce Tobacco Use, Save Lives and Generate Revenue - Guindon, G. Emmanuel; Perucic, Anne-Marie; Boisclair, David (World Bank, Washington, DC, 2013)
This report summarizes the health consequences and costs associated with tobacco use. It reviews price trends for tobacco products in Bangladesh, India, Indonesia, Nepal, Thailand and Sri Lanka. It reports trends in government tobacco tax revenues and how tobacco products are currently taxed in these countries, and in Maldives and Myanmar. The third section examines the demand for tobacco products in south-east Asian countries. A literature review on the demand for tobacco products in developing countries is followed by new analysis using time series and household-level data. The revenue-generating potential of tobacco taxes in south-east Asian countries is discussed. Finally, the report discusses contraband trade in tobacco products in South- East Asia, with emphasis on the industry's alleged role in smuggling.